Do whales have belly buttons? - Berger, Melvin; Berger, Gilda; Bond, Higgins (New York : Scholastic, 1999)
Provides answers to such questions about various species of whales and dolphins as "Do all whales have teeth?", "How long do most whales live?", "Why do dolphins whistle?", and "Can dolphins save humans?"
Keywords: Whales -- Miscellanea -- Juvenile literature; Whales -- Miscellanea; Questions and answers